Measurements of differential cross sections of Higgs boson production through gluon fusion in the $$H→ WW^{*}→ eν μ ν $$ H→WW∗→eνμν final state at $$\sqrt{s} = 13$$ s=13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Springer Open.